Analysis of Minor Proteins Present in Breast Milk by Using WGA Lectin - Iván Hernández-Caravaca; Andrés Cabañas; Rebeca López-Úbeda; Leopoldo González-Brusi; Ascensión Guillén-Martínez; Mª José Izquierdo-Rico; Mª Nieves Muñoz-Rodríguez; Manuel Avilés; Mª Jesús Ruiz García (MDPI AG, 2022)
Breast milk is a complex and dynamic biological fluid and considered an essential source of nutrition in early life. In its composition, the proteins have a relevant biological activity and are related to the multiple benefits demonstrated when compared with artificial milks derived from cow's milk. Understanding human milk composition provides an important tool for health care providers toward the management of infant feeding and the establishment of breastfeeding. In this work, a new technique was developed to increase the knowledge of human milk, because many of the components remain unknown. To isolate minor proteins present in breast milk by using WGA lectin, breast milk was centrifuged to remove cells and separate the fat phase from the serum phase. The serum obtained was separated into two groups: control (n = 3; whole serum sample from mature milk) and WGA lectin (n = 3; sample processed with WGA lectin to isolate glycosylated proteins). The samples were analyzed by high-performance liquid chromatography coupled to mass spectrometry (HPLC/MS). A total of 84 different proteins were identified from all of the samples. In the WGA lectin group, 55 different proteins were isolated, 77% of which had biological functions related to the immune response. Of these proteins, there were eight WGA lectin group exclusives, and two had not previously been described in breast milk (polyubiquitin-B and POTE ankyrin domain family member F). Isolation by WGA lectin is a useful technique to detect minor proteins in breast milk and to identify proteins that could not be observed in whole serum.